Страницы жизни Н. Н. Толстого и их отражение в повести «Хаджи-Мурат» - Белоусова, Е. В.
Автор статьи вводит в научно-текстологический оборот неизвестный архивный документ, послуживший одним из первоисточников к повести Л.Н. Толстого «Хаджи-Мурат» – «Формулярный список» участника Кавказской войны Н.Н. Толстого, старшего брата писателя. Дан сравнительно-сопоставительный анализ текстов повести и «Формулярного списка», в результате чего выявлено заимствование Л.Н. Толстым фактов из военной жизни брата и их творческое переосмысление. Приведён пример отступления писателем от исторической достоверности в пользу наибольшей художественной выразительности. The author of the article introduces into textological usage earlier unknown archive paper which served as one of the original sources for Leo Tolstoy while writing the novella “Hadji Murad”. This is “The service record book” of the participant of the Caucasus War which belonged to the elder brother Nikolay Tolstoy. Through comparatively-correlative method of the contents of the novella and “The service record book” the author brings striking evidence of the facts borrowed from Nikolay Tolstoy military career and their artistic reconception. The author gives an example how Leo Tolstoy deviates from historical originality in fa”vour of greater artistic expressiveness.
Keywords: Литературоведение